2019
DOI: 10.1002/jmri.26640
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of MR for hepatocellular carcinoma based on LI‐RADS v2018, compared with v2017

Abstract: Background The Liver Imaging Reporting and Data System (LI‐RADS) is widely adopted for noninvasive diagnosis of hepatocellular carcinoma (HCC). It's updated to version 2018 recently, with some major changes compared with v2017. However, the diagnostic performance of LI‐RADS v2018 and its difference with v2017 are yet to be validated. Purpose To compare the diagnostic performances of LI‐RADS on MR for diagnosing HCC between v2017 and v2018. Study Type Retrospective. Subjects In all, 181 patients with 217 hepati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
34
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 24 publications
(51 reference statements)
3
34
0
Order By: Relevance
“…This was due to the removal of the antecedent US visibility requirement, which made it easier to categorize 10‐19 mm observations as LR‐5. Our results are similar to those published by Ren et al who demonstrated in an Asian cohort primarily afflicted with chronic hepatitis B and in whom surgical resection is the main curative therapy, that with v2018 there were increased numbers of LR‐5 and LR‐3 observations and a reduction in LR‐4 observations . Our results are the first in a Western cohort, which primarily is afflicted with cirrhosis and in whom transplantation is the only curative option.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This was due to the removal of the antecedent US visibility requirement, which made it easier to categorize 10‐19 mm observations as LR‐5. Our results are similar to those published by Ren et al who demonstrated in an Asian cohort primarily afflicted with chronic hepatitis B and in whom surgical resection is the main curative therapy, that with v2018 there were increased numbers of LR‐5 and LR‐3 observations and a reduction in LR‐4 observations . Our results are the first in a Western cohort, which primarily is afflicted with cirrhosis and in whom transplantation is the only curative option.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, 1 high‐grade dysplastic nodule met the criteria for LR‐5 based on v2018 and not based on v2017, decreasing the point estimate for the PPV of the LR‐5 category from 100% to 96.4% in the subset of observations with available histology. The results are similar to the 2 retrospective studies using histology as the gold standard, which reported specificity of v2018 LR‐5 criteria to be 89%‐90% . However, the data thus far are available from single‐institution studies.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations